Nonlinear Simulation of the Hydrogen Atom Based on the Model of the Elliptic Oscillator - Santagata, C. (Нелінійні коливання, 2001)
It is shown that the application of the model of the hydrogen atom, which is based on the theory of the elliptic oscillator, makes it possible to describe the structure of electron orbits. The investigation is based on asymptotics methods of nonlinear mechanics. It was established that the stable orbits of the electron correspond to certain resonant states. A numerical simulation of the problem was carried out